Tafsīr Maqāsidī As an Alternative Method Legal Istinbāṭ - Hani Sholihah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The teachings of the Koran which are believed by ṣālih li kulli zamān wa makān are required to be able to provide solutions for every problem that arises in society. Meanwhile, Rasulullah saw. as an authoritative interpreter, does not interpret all the verses of the Qur'an. The existing interpretation methods, namely tafsīrbi al-ma'tsūr and interpretation bi al-ra'yi, are considered not fully able to answer various problems that arise in society. For this reason, modern scholars offer a method of interpretation as an alternative to the legal istinbāṭ method, the tafsīr maqāṣidī method. This study aims to further examine what and how tafsīr maqāṣidī is a method of interpretation as well as an alternative method of legal istinbāṭ. Using the library research method, various writings related to interpretation and ushul fiqh were studied and analyzed. The results of the study found that the maqāṣidī tafsīr is the interpretation of the Qur'an which uses maqāṣid al-syarī`ah as its interpretation approach. With the basis of al-maṣlaḥah as the core of maqāṣid al-syarī`ah, the maqāṣidī tafsīr method is expected to be more able to provide solutions to every problem that arises in society, so that Islamic teachings that are ṣālih li kulli zamān wa makān will be more widely felt.